Caracterización florística y predominancia de arvenses en el cultivo de maíz en dos zonas productoras de Manabí - Grijalva Villamar, Diego German (2021)
The objective of the work was to characterize the floristic composition and predominance of weeds in corn cultivation in two producing areas of Manabí. To estimate the dominance of the existing weeds, two localities of the Tosagua Canton (El Junco, Bachillero) were considered, selecting 10 properties, where thirty random samplings were carried out using a 0.50 x 0.50 m quadrant. At each sampling point, the existing weeds and their respective identification were counted. In the El junco locality, 47 species belonging to 21 botanical families were determined. Of the 47 species, 7 belong to the monocotyledonous class and 40 to the dicotyledonous class. The family that obtained the highest representativeness in this locality, with 62.88% belonging to Poaceae, 37.12% Cyperaceae, 28.21% Euphorbiaceae, 13.61% Asteraceae, 11.84% Malvaceae and 10.13% Fabaceae . In addition, the life cycle of each species was obtained, with 80.17% being represented by annual weeds and 19.83% by perennial weeds. The species with the highest density and frequency were: P. fasciculatum, E. hirta, C. laxus; C. cinereum, R. scabra, C. hirtus, A. guyensis, H. longiflora, P. paniculata. The highest dominance values were obtained for the species H. longiflora; P. fasciculatum, E. hirta and C. cinereum 4.19; 3.88; 3.49 and 3.38% respectively. On the other hand, the town of Bachillero obtained a total of 69 species that belong to 26 botanical families. Of which 14 belong to the monocotyledonous class and 55 to the dicotyledonous class. The families with the highest abundance of species were Poaceae with 85.23%, Amaranthaceae with 31.14%, Asteracea with 28.66% and Cyperaceae with 14.77%. According to their way of life, 88.80% are annual and 11.20% are perennial. The species with the highest density and frequency were: A. guyensis, C. cinereum, P. fasciculatum, E. indica, D. cordata, S. acuta, R. scabra, E. hirta, E. bonariensis, H. indicum, C hirtus, P. alliaceae, C. tora. The highest dominance values were reported for the species A. guyensis with 10.32%, C. cinereum with 10.76% and D. cordata with 10.35%.